The Effectiveness of Inquiry Contextual Learning Model on Student Science Process Skills in Food Microbiology in Biology Department, the State University of Medan - Henni Rahayu Siregar; Hasruddin Hasruddin; Martina Restuati (Proceedings of AICS - Social Sciences, 2017)
The objective of this study is to find out the effect of contextual inquiry learning model on student science process skills in food microbiology. A quasi experiment research with pretest-posttest control group design was used in this study. The population of this was 6th semester student biology department and two classes chosen as the sample by applying cluster random sampling technique. Experiment class was using contextual inquiry model as much as 42 students while control class was using direct learning model much as 40 students. The instrument used to obtain the data of student science process skill is with essay test. Technical analysis of data using Covariate Analysis at significant level α = 0.05 with the help of SPSS 22. The results showed that there was a significant contextual inquiry learning model to the students' science process skill (F = 22.760; P = 0.000). The students' science process skills that were taught by contextual inquiry (87.72 ± 5.129) were significantly higher than the direct learning model. As a follow up of the results of this study, it is expected to apply contextual inquiry model on food microbiology material in an effort to improve the skill of science process.